Analysis of Production Machine Effectiveness in Line A Using OEE and Six Big Losses Method - Muhammad Iqbal Gymnastiar; Ridwan Hartono (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
The operational effectiveness of production machines is crucial in maintaining the smoothness and efficiency of manufacturing processes. This research aims to analyze the effectiveness of the production system on Line A at PT XYZ using the Overall Equipment Effectiveness (OEE) method and the Six Big Losses approach, and identify the dominant factors causing equipment failure losses. Data was collected from January to May 2024, covering quantitative analysis of availability, performance, and quality values. The results show that the average OEE value is 82.58%, which is still below the world-class standard of 85%. Of the total loss time of 20,367 minutes, the highest losses came from equipment failure losses at 38.25%, reduced speed losses (23.58%), and idling and minor stoppage losses (14.36%). These findings indicate that technical machine disruptions are the leading cause of the decline in production effectiveness. Therefore, improvement strategies need to focus on strengthening preventive and predictive maintenance systems, enhancing technician competency, and optimizing the reporting and handling of disruptions to improve the efficiency and reliability of the production system sustainably.